Prognostic value of presepsin (soluble CD14-subtype) in diagnosis of ventilator-associated pneumonia and sepsis in trauma patients - Jovanović Bojan; Đurić Olivera; Marković-Denić Ljiljana; Isaković Aleksandra; Doklestić Krstina; Stanković Sanja; Vidičević Sašenka; Palibrk Ivan; Samardžić Janko; Bumbaširević Vesna (Vojnosanitetski Pregled)
Background/Aim. Presepsin (soluble CD14-subtype) is a fragment of CD14 produced in response to bacterial infections and a novel biomarker of pneumonia, sepsis and septic shock. The aim of this study was to compare sensitivity and specificity of persepsin, soluble CD14-subtype (sCD14-ST) with other biomarkers: procalcitonine (PCT), C-reactive protein (CRP) and leukocyte count (Le) in mechanically ventilated injured patients, as a marker of pneumonia, sepsis and septic shock. Methods. The prospective study was undertaken in trauma and surgery intensive care unit of the Emergency Center, the Clinical Center of Serbia from January to April 2013. The study included 39 trauma patients requiring mechanical ventilation, and who developed one of the following inclusion criteria: Systemic Inflammatory Response Syndrome (SIRS), ventilator associated pneumonia (VAP), sepsis and/or septic shock. On admission Acute Physiology and Chronic Health Evaluation II (APACHE II) Score and Injury Severity Score (ISS) were calculated. Seventy-two measurements of four biomarkers (presepsin, PCT, CRP and Le) were performed in 39 patients at the moments of diagnosis of SIRS, VAP, sepsis and/or septic shock (21 when SIRS diagnosis was established, 21 after the diagnosis of VAP, 18 at the moment of diagnosis of sepsis and the remaining 12 measurements were conducted while diagnosing the septic shock). The Sequential Organ Failure Assessment (SOFA) score was calculated at these points as well. Results. Patients were mainly severely injured (mean ISS = 24.2) and had moderately severe medical condition at admission (mean Apache II score, 14.5). Presepsin concentration significantly differed among all the four groups, except between sepsis and septic shock. The strongest positive correlation of presepsin evinced with PCT (r = 0.741, p < 0.001). The sCD14-ST indicated better performance in diagnosis of both VAP (AUC = 0.909) and sepsis (AUC = 0.899), compared to PCT (AUCs: 0.863, 0.885, respectively), CRP (AUCs: 0.703, 0.677, respectively) and Le (AUCs: 0.668, 0.700, respectively). Conclusion. This study revealed that sCD14-ST is a reliable biomarker for distinguishing sepsis severity. It also showed a good correlation with the infection development as well as worsening in injured patients. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no.175046]